2010
DOI: 10.5433/1679-0359.2010v31n2p313
|View full text |Cite
|
Sign up to set email alerts
|

<b>Quebra de dormência em macieiras 'Fuji Kiku' com uso de extrato de alho</b>

Abstract: ResumoA utilização de produtos químicos, que promovam e uniformizem a brotação e a floração, em frutíferas de clima temperado vem trazendo grande preocupação devido ao seu efeito tóxico para o homem e pela dependência de poucos produtos para essa finalidade. No intuito de buscar uma solução para esse problema, o experimento foi instalado em pomar comercial de macieiras 'Fuji kiku' no município de Guarapuava-PR, utilizando os seguintes tratamentos:Foram avaliadas as seguintes variáveis: porcentagem de brotação,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
2
Order By: Relevance
“…Garlic is efficient to break dormancy, since its extract is rich in diallyl disulfide, a compound that destroys glutathione and increases H 2 O 2 levels when in contact with buds. As a result, it leads to respiratory alteration, inhibits glucose enzymes, changes carbon flow, triggers metabolic modifications and favors the expression of SNF-like protein-kinases, which transfer the signal that ends bud dormancy (PERUSSI, 2010;El-AMARY and EL-HAMIED, 2018). Low efficiency of Welsh onion as a budburst inducer may be a result from the fact that it does not have high concentrations of diallyl disulfide.…”
Section: Resultsmentioning
confidence: 99%
“…Garlic is efficient to break dormancy, since its extract is rich in diallyl disulfide, a compound that destroys glutathione and increases H 2 O 2 levels when in contact with buds. As a result, it leads to respiratory alteration, inhibits glucose enzymes, changes carbon flow, triggers metabolic modifications and favors the expression of SNF-like protein-kinases, which transfer the signal that ends bud dormancy (PERUSSI, 2010;El-AMARY and EL-HAMIED, 2018). Low efficiency of Welsh onion as a budburst inducer may be a result from the fact that it does not have high concentrations of diallyl disulfide.…”
Section: Resultsmentioning
confidence: 99%
“…D e E, que anteriormente( Figura 4). Em macieiras cultivar "Kiku", Perussi, et. al., (2010) verificaram que todos os tratamentos com extrato de alho na região de Guarapuava-PR tiveram efeito na superação da dormência, conforme o observado neste experimento, com a cultura da nogueira pecan.…”
Section: Resultsunclassified
“…Dependence on hydrogenated cyanamide is a problem that affects all temperate fruit trees. Perussi et al (2010) studied the effect of garlic extract (GE) on dormancy break in apple trees (Malus domestica) and carried out an experiment in which one of the treatments was hydrogenated cyanamide. They concluded that the rest-breaking agents that led to the highest budbreak average were Bioalho (GE, Natural Rural S.A.) mixed with mineral oil (MO) and natural garlic (a product which results from garlic extraction by cold pressing) mixed with MO.…”
Section: Actinidia Deliciosa Ecophysiologymentioning
confidence: 99%
“…These, when applied to the bud, cause an increase in H 2 O 2 levels, inducing oxidative stress and subsequently budding sprouting. There is also another theory, described by Perussi et al (2010), where garlic contains allyl alcohol, which converts into a toxic aldehyde when it undergoes oxidation by the enzyme alcohol dehydrogenase, destroys glutathione and, consequently, increases H 2 O 2 levels. This process triggers many metabolic changes and does not keep buds in the dormancy stage.…”
Section: Actinidia Deliciosa Ecophysiologymentioning
confidence: 99%